2021
DOI: 10.3390/ijerph18062802
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace Interventions, Stress and Cortisol: A Scoping Review

Abstract: Background: Engaging with nature can profoundly impact psychological and physiological health of persons across the lifespan. Greenspace interventions (GSI) encompass a broad range of strategic, nature-based activities for overall health and wellbeing. Within the past 20 years there has been a growing interest in the access to and management of greenspace to mediate the deleterious impact of acute and chronic stress, particularly, physiologic biomarkers of stress such as cortisol. Objective: This review aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 68 publications
(115 reference statements)
0
33
0
Order By: Relevance
“…The observed decreases in salivary cortisol on the intervention days were aligned with other studies where typically decreases of ~5% in cortisol levels have been observed in a variety of natural settings. 42 A recent study of non-facilitated visits at sensory garden resulted in even greater (16% cf 5%) intervention effect on salivary cortisol. 47 The presence of a statistically significant decrease in cortisol on intervention days versus non-intervention days, despite a low statistical power, does suggest potential contribution of NBI to the moderation of stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decreases in salivary cortisol on the intervention days were aligned with other studies where typically decreases of ~5% in cortisol levels have been observed in a variety of natural settings. 42 A recent study of non-facilitated visits at sensory garden resulted in even greater (16% cf 5%) intervention effect on salivary cortisol. 47 The presence of a statistically significant decrease in cortisol on intervention days versus non-intervention days, despite a low statistical power, does suggest potential contribution of NBI to the moderation of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The most studies have detected decreasing effect of nature settings on participants’ salivary cortisol levels. 42 Salivary α-amylase is much less studied and depending on the type and physical strenuosity of the intervention, either increase or decrease of α-amylase during the intervention has been detected. 43–45 …”
Section: Discussionmentioning
confidence: 99%
“…It appears that greenspace interventions can also reduce cortisol and stress levels, yet most studies on this topic are limited by data collection methods and heterogeneity of the study design. [ 9 ] Although more research is needed, the current data would suggest that greenspace exposure is associated with numerous health benefits, enough to encourage policymakers and urban planners to create, design and maintain accessible greenspaces in urban centers.…”
Section: Shinrin-yoku and Greenspace Interventionsmentioning
confidence: 99%
“…The practice of spending time amongst the trees is known in Japan as Shinrin-yoku or ‘forest-bathing’ and has been shown to be of therapeutic benefit with regards to improving mental and immune system health. In fact, the many documented physiological benefits of forest bathing include among others, a decrease in both pulse rate and cortisol levels which can affect the proper functioning of the immune system (Timko et al 2020 ; Ochiai 2019 ) and which have brought interest for further study (Jones et al 2021 ). In many other parts of the world, the benefits of walking in a wooded area is known but a medical approach that hands out such ‘green prescriptions’ is not common practice.…”
Section: The Medicines We Breathe; Forests As a Cornucopia Of Pharmaceutical Potentialmentioning
confidence: 99%